Ability of electrical stimulation therapy to improve the effectiveness of robotic training for paretic upper limbs in patients with stroke. Issue 11 (November 2016) - Miyasaka, Hiroyuki; Orand, Abbas; Ohnishi, Hitoshi; Tanino, Genichi; Takeda, Kotaro; Sonoda, Shigeru
Highlights: The effect of robot-aided training combined with NMES on the hemiparetic upper limbs after stroke was investigated. The robot training with NMES group showed significant improvement in active ROM compared with robot only training group. The robot-aided training with NMES was more effective for recovery from hemiparesis than robot only training. Abstract: We investigated whether untriggered neuromuscular electrical stimulation (NMES) can increase the effectiveness of shoulder and elbow robotic training in patients with hemiparesis. Thirty subacute stroke patients were randomly equally allocated to robot only (RO) and robot and electrical stimulation (RE) groups. During training, shoulder and elbow movements were trained by operating the robotic arm with the paretic arm, and the robotic device helped to move the arm. In the RE group, the anterior deltoid and triceps brachii muscles were electrically stimulated at sub-motor threshold intensity. Training was performed (approximately 1 h/day, 5 days/week for 2 weeks) in addition to regular rehabilitation. Active range of motion (ROM) values of shoulder flexion and abduction, and Fugl-Meyer assessment (FMA) scores were measured before and after training. Active shoulder ROM was significantly better after than before training in the RE group; however, no such improvement was noted in the RO group. FMA scores were significantly better in both groups, and there was no significant difference between the groups. Untriggered NMES might increase the effectiveness of shoulder and elbow robotic training in patients with hemiparesis. Additionally, NMES at a sub-motor threshold during robotic training might facilitate activation of paretic muscles, resulting in paralysis improvement.